CONVERSION FACTOR FROM DOSEMETER READING TO AIR KERMA FOR NUCLEAR WORKER USING ANTHROPOMORPHIC PHANTOM FOR FURTHER CONVERSION FROM AIR KERMA TO ORGAN-ABSORBED DOSE. Issue 3 (4th May 2020) - Furuta, Hiroshige; Tsujimura, Norio; Nishide, Akemi; Kudo, Shin'ichi; Saigusa, Shin
Abstract: Estimation of cancer risk based on the organ-absorbed dose is underway for the Japanese Epidemiological Study on Low-Dose Radiation Effects (J-EPISODE). The reconstruction method for the organ-absorbed dose follows the approach adopted in the IARC 15-Country Collaborative Study, which examined the dosemeter response to photon exposure for the old film badge (FB) type, a multi-element FB and a thermoluminescence dosemeter. Until 2000, the dosemeters used in Japan were almost the same in the IARC study, so IARC study data could be used as they were. However, since 2000, the type of dosemeter has been replaced with active personal dosemeters (hereafter called electronic personal dosemeters), radio-photoluminescent glass dosemeters (Glass badge) and optically stimulated luminescence dosemeters (Luminess badge). Hence, it was necessary to collect these data again. A dosemeter response experiment was conducted using a device that irradiated an anthropomorphic phantom in the Japan Atomic Energy Agency calibration laboratories. The aim of the paper is to provide a conversion factor from reading in terms of H p (10) to air kerma for realistic conditions for further conversion from air kerma to organ-absorbed dose. The obtained dosemeter responses for the dosemeter types currently used in Japan were consistent with those in the IARC study. These data will be utilized for J-EPISODE in reconstructing the organ-absorbed dose.